2021
DOI: 10.1155/2021/6617381
|View full text |Cite
|
Sign up to set email alerts
|

Road Traffic Injuries and Related Safety Measures: A Multicentre Analysis at Military Hospitals in Tabuk, Saudi Arabia

Abstract: Background. Road traffic injuries are one of the major public safety issues around the world, as they put a great burden on countries’ economies. Saudi Arabia has a good road transportation system, but still, road-related fatalities are higher in this country. The main purpose of this study was to determine the association between the severity of injuries caused by road traffic collision and safety measures taken by the drivers admitted to the emergency departments at two military hospitals in Tabuk, a city in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 30 publications
(39 reference statements)
1
9
0
Order By: Relevance
“…The study showed that bus drivers who do not obey traffic rules are more likely to cause a fatality than a non-injury during a bus accident. This result is consistent with previous studies [ 48 ], which demonstrated that bus drivers not obeying traffic rules tend to experience more severe injuries. The results revealed that bus drivers who are drunk while driving are more likely to cause a fatality than a non-injury in bus accidents.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The study showed that bus drivers who do not obey traffic rules are more likely to cause a fatality than a non-injury during a bus accident. This result is consistent with previous studies [ 48 ], which demonstrated that bus drivers not obeying traffic rules tend to experience more severe injuries. The results revealed that bus drivers who are drunk while driving are more likely to cause a fatality than a non-injury in bus accidents.…”
Section: Discussionsupporting
confidence: 94%
“…In contrast, Prato CG et al [ 19 ] reported that high speed limits may increase bus accident severity. A recent study on road traffic injuries showed that drivers driving at excessive speeds were two to three times more likely to cause severe injuries [ 48 , 51 ]. The results of the model also showed that bus drivers who attempted to overtake another vehicle or displayed abrupt maneuvers were more likely to cause a fatality compared to a non-injury, which is consistent with a previous study [ 48 ], which demonstrated that those who were abrupt driving were more than two times likely to be more severe injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a study in Qassim concluded that the most common injuries involved the head and neck, followed by the lower limbs [ 21 ]. This variation in literature may be attributed to a multitude of regional factors that may influence the mechanism of injury, such as the average driver’s road experience, the nature of roads in urban versus rural areas [ 22 ], and the availability of speed cameras [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Socio-demographic characteristics of participants: The socio-demographic information of participants from nine distinct studies is included in Table 1, which summarises the large number of cases from references [20][21][22][23][24][25][26][27][28]. These studies' geographic scope is constrained because they were all selected within Saudi Arabia's regions, like the Aseer region [22], Al Kharj [23], Riyadh [24,26], Tabuk [25], Eastern Province [27], and Ha'il [28]. The research methodology of the reviewed studies [23,[25][26][27] used a cross-sectional design; one study [20] was Analysis of national data, and the others [21,22,24,28] were retrospective studies.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%